A cultural selection analysis of human-dog interactions – A primer. Issue 2 (3rd July 2021) - Pfaller-Sadovsky, Nicole; Hurtado-Parrado, Camilo
ABSTRACT: Mounting interest in the evolutionary and contemporary aspects of human-dog association has resulted in growing research efforts from different disciplines. Despite its potential to contribute, behavior-analytic research efforts are scarce. We illustrate how the behavior-analytic three-level selection by consequences framework could inform research on human-dog interactions. The notions of interlocking behavioral contingencies and metacontingencies are applied to interpret specific interactions and suggest potential lines of research. We first analyze the development of cooperative human-dog hunting, and its implications for interspecific social-communicative skills. Second, we discuss contemporary family interactions between parents, children and dogs via an analysis of a prototypic social episode. Lastly, we provide an overview of the main approaches that have contributed to the understanding of human-dog interactions (e.g., anthrozoological), and show how their findings can be placed within the behavior-analytic framework. The selectionist framework is a cohesive approach that can importantly contribute to synthesize a large amount of scattered research on human-dog relationships conducted across various fields, and may inform further research applications.